2019
DOI: 10.1186/s42269-019-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative finite analysis of the mechanical behavior of ProTaper NEXT and WaveOne rotary files

Abstract: Finite element analysis was used to evaluate the stress distribution, estimate the residual stresses, bending, and amount of displacement of two nickel-titanium instruments manufactured by the same M-wire technology but with different cross-section. Materials and methods: Two brands of Ni-Ti instruments ProTaper NEXT (Dentsply Maillefer), and WaveOne (Dentsply Maillefer, Ballaigues, Switzerland) were scanned with stereomicroscope to produce a two-dimensional model for each file using computer-aided design prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Although metallurgical properties and metallurgical treatments have been shown to influence the properties of NiTi endodontic rotary instruments, geometrical design has been highlighted to be directly related to the stiffness [41], clinical efficiency and cutting performance of endodontic rotary files [29,42]. The cross-section design of endodontic rotary files has experienced a continuous development; Versluis et al reported that increasing the cross-sectional surface area lead to a decrease in the flexibility of endodontic rotary files by a stress accumulation at the upper and lower edges of the cross section during bending tests, compared with smaller cross-sectional surface areas [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although metallurgical properties and metallurgical treatments have been shown to influence the properties of NiTi endodontic rotary instruments, geometrical design has been highlighted to be directly related to the stiffness [41], clinical efficiency and cutting performance of endodontic rotary files [29,42]. The cross-section design of endodontic rotary files has experienced a continuous development; Versluis et al reported that increasing the cross-sectional surface area lead to a decrease in the flexibility of endodontic rotary files by a stress accumulation at the upper and lower edges of the cross section during bending tests, compared with smaller cross-sectional surface areas [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the PTN system was used in continuous rotation movement that was reported to enhance the coronal carriage of dentine debris and chips via acting as a screw conveyor (23) . Besides, the WOG has a parallelogram cross section (4) , while PTN has a rectangular cross section (24) .…”
Section: Discussionmentioning
confidence: 99%